Upaya Peningkatan Produktivitas Petani Tembakau Melalui Diversifikasi Budidaya Sayur-Sayuran di Luar Musim di Desa Mujur Lombok Tengah NTB - Ngawit, I Ketut; Supeno, Bambang; Jihadi, Amrul (Jurnal Gema Ngabdi, 2024)
Efforts to improve the welfare of tobacco farmers require efforts that focus on increasing income, education, access to technology and information. One way is through diversifying vegetable crops outside the season, to get high prices. The problem is that soil fertility decreases due to water saturation resulting in poor aeration, solid structure and low soil pH. For this reason, counseling and assistance is carried out which aims to increase farmers' knowledge and skills in cultivating vegetable crops outside the season. The participatory action activity method was carried out for 5 months, through several stages, namely, problem identification, implementation, monitoring and evaluation. Counseling and mentoring activities take place in an orderly, safe and smooth manner. Farmers' knowledge and skills have increased, as evidenced by their high participation and enthusiasm in cultivating out-of-season vegetables. The application of agronomic measures such as the use of plastic mulch, organic fertilizer 20 - 25 tons ha-1 and NPK Ponska 75 - 150 kg ha-1, provides higher yields of mustard greens, tomatoes, chilies and shallots compared to the application of NPK Ponska 300 kg ha-1 without organic fertilizer and mulch. The income and profit from cultivating pakchoy, tomatoes, chilies and shallots is more than cultivating spinach, long beans and sweet corn, because the selling value is more expensive and stable with each price, pakchoy Rp. 12,500,- kg-1, tomatoes Rp. 8,500,- kg-1, chilies Rp. 25,000,- kg-1, and shallots Rp. 40,000,- kg-1.